An Interactive Intuitionistic Fuzzy Method for Multilevel Linear Programming Problems - Huang, Chan; Fang, Debin; Wan, Zhongping (Wuhan University journal of natural sciences, 2015)
In this paper, we propose an interactive method for solving the multilevel linear programming problems based on the intuitionistic fuzzy set theory. Firstly, the membership function and the non-membership function are introduced to describe the uncertainty of the decision makers. Secondly, a satisfactory solution is derived by updating the minimum satisfactory degrees with considerations of the overall satisfactory balance among all levels. In addition, the steps of the proposed method are given in this paper. Finally, numerical examples illustrate the feasibility of this method.